PERANAN ALI MOERTOPO BIDANG MILITER DAN POLITIK DALAM UPAYA MEWUJUDKAN STABILITAS NASIONAL INDONESIA TAHUN 1950-1984 - Hasan Bisri; Bobi Hidayat (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The problem in this research is the role of Ali Moertopo military and political fields in efforts to achieve national stability. The method used in this study is the historical method to conduct library research. Data collection techniques in this study using the steps of heuristics and the study of literature. In testing the correctness of the data or the validity of the data collection used internal and external criticism, while for the method of data analysis is the interpretation and historiography. The results of this study are (1) The role of the military in the field Ali Moertopo efforts to realize national stability Indonesia is conducting an insurgency against the PRRI / PERMESTA Because they can threaten the unity and integrity of the country. This makes the insurgency chaos and panic so do government crackdown by the military road and finally the uprising could be solved so that the creation of a national stability Indonesia. (2) Role Ali Moertopo politics in efforts to realize national stability of Indonesia is to help the course of politics, a period that also Ali Moertopo assigned Golkar in the first election. And also simplifying the political parties to be more effective in the next general election.